Harnessing Web 2.0 for ERP Implementations - Wu, Harris; Cao, Lan; Wu, Harris; Cao, Lan (IEEE software, 2016)
ERP implementations cost billions of dollars annually in United States alone. This article describes how Web 2.0 may be used to reduce the cost, improve the quality and lower the risk of ERP implementations. Challenges and requirements for a web 2.0 knowledge repository system are gathered from ERP implementation communities through a case study. To fulfill these requirements, the article presents EPICS, a web 2.0 system that supports knowledge reuse in ERP implementations. A prototype is built upon a number of popular open source software packages. Prototype deployment at a real-world ERP community shows promising results. Besides cost savings, interesting business models emerge as a result of the deployment.